The Relationship Between Intellectual Property and Economic Development from An Islamic Perspective - Faten Shahin; Zurina Kefeli (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
This article aims to study the relationship between the components of intellectual property, which includes the trademark and patent, and economic development from the Islamic perspective. The article showed that the trademark distinguishes economic goods and services, showing that the Islamic religion is concerned with preserving the rights of owning goods. The Islamic religion emphasized the exclusive rights of goods that owned by merchants by distinguishing them with a trademark that guarantees the rights of its owner. The article also shows solid legal evidence for distinguishing goods and services, which is equivalent in this era to the legal registration of a trademark. The aim of the Islamic religion was to encourage fair economic competition, develop economic sectors, and encourage research and development. The study also showed the interest of the Islamic religion in patents and innovation. The Islamic religion is the religion of balance and creativity which emphasized the need to develop innovation through the presence of legal evidence in the Qur’an and Sunnah. The Islamic religion also showed that inventions are a main pillar in encouraging investment and building the Islamic economy, through the innovation of goods and services that serve society. In this article, the researcher used the descriptive method to study the relationship between intellectual property and economic development from an Islamic perspective. The results proved the interest of the Islamic religion in intellectual property in the giving the owners their rights and the prohibition of attacking it by non-owners. The Islamic religion, through its legislation in the Qur’an and Sunnah, encouraged the construction of intellectual property as a prerequisite for the development of the economy.